Recovering the Female Voice in Islamic Scripture - Bahar Davary (International Institute of Islamic Thought, 2015)
The absence of women’s voices from the scriptures of the major world religions has been the subject of feminist theologians’ inquiry, especially during the past three decades. Georgina Jardim’s work in feminist scholarship and women’s study is impressive. This book provides a fine synopsis of some of the important works in Islamic hermeneutical tradition while set in a comparative framework. As such, it is a great contribution to the comparative feminist hermeneutics of scripture. The author makes good use of works by Amina Wadud, Barbara Stowasser, Asma Barlas, and other feminists who have worked on the Qur’an or on paradigms of Muslim women in the Islamic textual tradition. She weaves their ideas and theories with those of Annemarie Schimmel, Sachiko Murata, Denise A. Spellberg, W. Montgomery Watt, Richard Bell, Ashley M. Walker, Michael Sells, and others. In addition, she draws from Christian and Jewish feminist thought as well as that of secular philosophers or theoreticians in juxtaposition with Muslim interpretations. As the title suggests, she focuses on women’s speech by emphasizing voice rather than silence. The author concludes that women not only have a voice in Islamic scripture, but that in the Abrahamic scriptures as a whole they break silence in order to invoke social justice. The book’s predominant theme, the Qur’anic account of “the woman who disputes,” is juxtaposed with similar stories in the Jewish and Christian scriptures, which makes it an interesting exploration in Abrahamic interfeminist interreligious dialogue. Her use of scriptural reasoning to bring Abrahamic and secular voices in conversation on this topic is original. Among the few works with a comparative hermeneutic approach to women in religion are Murata’s The Tao of Islam (1992), a sourcebook on gender relations in Islamic discourse with references and analogies to the yin and yang elements, and Yvonne Yazbek Haddad and John L. Esposito’s Daughters of Abraham (2002). Jardim’s book is distinct in that it compares both feminist methodologies as well as a parallel scriptural story in these three traditions ...